Participation of the Kalitanjung Indigenous Community in Supervision of the 2019 Election in Banyumas Regency - Yon Daryono; Wahju Gunawan; Ari Ganjar Herdiansah (Asia-Pacific Journal of Elections and Democracy, 2022)
Indigenous communities in elections in Indonesia are very important for the legitimacy of the election results. The role of indigenous communities has often been used for voter participation. However, election organizers, political parties, and the government rarely discuss the role of indigenous communities as election monitors or supervisors. This article outlines how the involvement and civic engagement carried out by the Election Supervisory Agency (Bawaslu) contributed to the participation of the Kalitanjung indigenous community in the supervision of the 2019 presidential and legislative elections. This study employs a qualitative method with data collection techniques through interviews and literature studies. The conclusion of the results of the study shows that the indigenous people of Kalitanjung have already obeyed norms, cultures, and traditions about behaving kindness according to the message of the lelulur, such as steadfast waton (obedient to the leader and the legitimate government), not jumawa (arrogant), not disbursing (taking the goods and rights of others), and being ready to die as cool as urip (can die at that time) if it violates the rules. They also respect state regulations in the form of election laws in their capacity as Indonesian citizens.